2012
DOI: 10.1002/ps.3244
|View full text |Cite
|
Sign up to set email alerts
|

Designer repellents: combining olfactory, visual or taste cues with a secondary repellent to deter free‐ranging house sparrows from feeding

Abstract: These data demonstrate the potential of combining the secondary repellent AQ with additional salient cues for modifying the feeding behaviour of sparrows.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…Some learning of pellet-associated cues was demonstrated by captive native kea, which ate less pellet bait with cinnamon pre-exposure to similar pellets containing anthraquinone and/ or d-pulegone than post-exposure (Orr-Walker et al 2012). However, relative to plain wheat, the amount of blue-dyed wheat with anthraquinone eaten by sparrows was not further reduced by the addition of cinnamon, suggesting little role for cinnamon as a learning cue (Clapperton et al 2012). Currently, baits are dyed a uniform colour; countershading (i.e.…”
Section: Synthesis and Recommendationsmentioning
confidence: 96%
See 2 more Smart Citations
“…Some learning of pellet-associated cues was demonstrated by captive native kea, which ate less pellet bait with cinnamon pre-exposure to similar pellets containing anthraquinone and/ or d-pulegone than post-exposure (Orr-Walker et al 2012). However, relative to plain wheat, the amount of blue-dyed wheat with anthraquinone eaten by sparrows was not further reduced by the addition of cinnamon, suggesting little role for cinnamon as a learning cue (Clapperton et al 2012). Currently, baits are dyed a uniform colour; countershading (i.e.…”
Section: Synthesis and Recommendationsmentioning
confidence: 96%
“…Brown and Ulrich (2005) reviewed parameters affecting the efficacy of aerial 1080 operations for possum and rat control and concluded that research was required on the relative benefits of using green-and blue-dyed baits for protection of native birds. Blue dye was suggested as an alternative because some research (Hartley et al 1999(Hartley et al , 2000Clapperton et al 2012) indicated blue dye was more effective than green in deterring some bird species from feeding on bait.…”
Section: Background Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…Day et al (2003) commented that the level of pecking observed may have resulted in some deaths of robins had the baits been toxic. Clapperton et al (2014) found a similar but greater reduction in pecking of baits soaked in repellent (0.09% anthraquinone), although avoidance may have been enhanced by the inclusion of blue dye in the baits (Clapperton et al 2011). Blue dye may be less attractive to some birds than the green dye used in operational control baits (Hartley et al 1999).…”
Section: Relevance For Other Native Birdsmentioning
confidence: 99%
“…The initial focus on repellents to reduce the risk of poisoning of kea was on d-pulegone as a primary repellent and anthraquinone as a secondary repellent (Orr-Walker et al 2012; Cowan et al 2015), a strategy shown to be effective for crop protection and for deterring North Island robins (Petroica longipes) and tomtits (P. macrocephala) from pecking at pest control baits (Day et al 2003;Clapperton et al 2011Clapperton et al , 2014Day et al 2012). However, laboratory and field trials demonstrated that anthraquinone reduced cereal bait consumption by rats at concentrations of 0.1% and 0.25% and hence the efficacy of 1080 cereal pellets for rat control (Cowan et al 2015;Crowell et al 2015b).…”
Section: Introductionmentioning
confidence: 99%